The information content of earnings and prices: A simultaneous equations approach - Beaver, William H.; McAnally, Mary Lea; Stinson, Christopher H. (Journal of Accounting and Economics, 1997)
The price-earnings relation can be characterized as a system of simultaneous equations. Earnings and prices can behave as if they are both endogenously determined because they are jointly affected by information that is difficult to specify explicitly. Specification tests provide evidence that both earnings changes and price changes are endogenous. The price and earnings coefficients increase from OLS to joint estimation and, under a restrictive set of assumptions, provide increasingly similar estimates of the permanent component of earnings. The evidence is consistent with the contention that a portion of the single-equation bias can be mitigated via joint estimation.